Hybrid Nanofillers Creating the Stable PVDF Nanocomposite Films and Their Effect on the Friction and Mechanical Properties - Čech Barabaszová, Karla; Holešová, Sylva; Plesník, Lukáš; Kolská, Zdeňka; Joszko, Kamil; Gzik-Zroska, Bożena (Polymers, 2022)
The solvent casting method was used for five types of polyvinylidene difluoride (PVDF) nanocomposite film preparation. The effect of nanofillers in PVDF nanocomposite films on the structural, phase, and friction and mechanical properties was examined and compared with that of the natural PVDF film. The surface topography of PVDF nanocomposite films was investigated using a scanning electron microscope (SEM) and correlative imaging (CPEM, combinate AFM and SEM). A selection of 2D CPEM images was used for a detailed study of the spherulitic morphologies (grains size around 6-10 μm) and surface roughness (value of 50-68 nm). The chemical interactions were evaluated by Fourier transform infrared spectroscopy (FTIR). Dominant polar γ-phase in the original PVDF, PVDF_ZnO and PVDF_ZnO/V, the most stable non-polar α-phase in the PVDF_V_CH nanocomposite film and mixture of γ and α phases in the PVDF_V and PVDF_ZnO/V_CH nanocomposite films were confirmed. Moderately hydrophilic PVDF nanocomposite films with water contact angle values (WCA) in the range of 58°-69° showed surface stability with respect to the Zeta potential values. The effect of positive or negative Zeta-potential values of nanofillers (ζn) on the resulting negative Zeta-potential values (ζ) of PVDF nanocomposite films was demonstrated. Interaction of PVDF chains with hydroxy groups of vermiculite and amino and imino groups of CH caused transformation of γ-phase to α. The friction properties were evaluated based on the wear testing and mechanical properties were evaluated from the tensile tests based on Young's modulus (E) and tensile strength (Rm) values. Used nanofillers caused decreasing of friction and mechanical properties of PVDF nanocomposite material films.
Keywords: chlorhexidine; zinc oxide; friction and mechanical properties; PVDF nanocomposite films; Zeta-potential values; nanofillers; correlative imaging; vermiculite; surface roundness